The Concept of Mushawwibah and Mukhaththiah as Development of Contracts in Sharia Financial Institutions - Muhammad Yunus; Rani Mariana; Ending Solehudin (al-Afkar, Journal For Islamic Studies, 2024)
In this paper the author tries to explore how Islamic epistemology, through a study in the field of ushul fiqh, namely the concept of Mushawwibah and Mukhaththiah as the development of contracts in Islamic financial institutions. Understanding this issue is very important, considering that currently so many people are calling for the need for renewal in the field of fiqh because of the demands of the times and human needs in the field of dynamic muamalah. We should not abandon the scientific treasures of the classical century and should not rush to reject new things before understanding them properly and correctly with the Mushawwibah and Mukhaththiah Theory in Ushul Fiqh. Ushul Fiqh is more capable of entering the sides of legal issues related to the behavior of Muslims in all aspects including in the field of muamalah. So for followers of the mushawwibah theory, it is explained that all the different conclusions, the correct one is not one, in fact they can all be correct. This is so if all the mujtahids display a framework of thinking that is in line with the ushul-fiqh path. Whereas the followers of mukhaththiah argue that all the many conclusions, the correct one is only one, especially if some of the conclusions have contradictory values. This research found that Islam examines all texts both implied in the Qur'an and al-Hadith, both in the form of zhanni (conjecture), thus the meaning that emerges from the text is always formulated in different conclusions, meaning that it is still mukhtalaf fih or there are differences of opinion.